Framing Analysis of Racism Issue Coverage of K-Pop Girl Group Kiss of Life in Tempo Online Media - Elena Dwi Rostanti; Khaerudin Imawan; Yanto Heryanto (Greenation Research & Yayasan Global Resarch National, 2026)
This study explores how Tempo.co framed the issue of racism involving the K-pop girl group Kiss of Life following a live broadcast themed “old-school hip hop vibes” in April 2025. The controversy emerged after the group was accused of cultural appropriation toward the Black community, resulting in the loss of more than 200,000 social media followers. The purpose of this study is to understand the framing strategy employed by Tempo.co and its impact on readers’ perceptions in Indonesia. The study applies framing analysis based on the model developed by Robert N. Entman, using a descriptive qualitative approach. The data consist of four Tempo.co articles published between April 6 and 9, 2025, complemented by in-depth interviews with fans of Kiss of Life. The findings indicate that Tempo.co consistently framed the case as a serious issue of racism through four key framing elements: defining the problem as cultural appropriation, diagnosing the cause as cultural ignorance, making moral judgments from various public perspectives, and emphasizing the perceived inadequacy of the group’s apology. This framing was found to be effective in enhancing readers’ understanding of the complexity of racism within the K-pop industry, while maintaining journalistic neutrality.